2015
DOI: 10.20533/ijels.2046.4568.2015.0057
|View full text |Cite
|
Sign up to set email alerts
|

New Approaches to E-Cognitive Assessment of E-Learning

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
0
8
0
1
Order By: Relevance
“…Uno de los retos del presente siglo es la creación e innovación de nuevos medios de valoración del aprendizaje que vayan más allá del encapsulamiento digital de las herramientas de evaluación que están disponibles desde el siglo pasado (exámenes, portafolios, rúbricas, etc.) (Morales-Martínez, López-Ramírez y López-González, 2015).…”
Section: Introductionunclassified
“…Uno de los retos del presente siglo es la creación e innovación de nuevos medios de valoración del aprendizaje que vayan más allá del encapsulamiento digital de las herramientas de evaluación que están disponibles desde el siglo pasado (exámenes, portafolios, rúbricas, etc.) (Morales-Martínez, López-Ramírez y López-González, 2015).…”
Section: Introductionunclassified
“…Cognitive psychology includes a wide range of techniques used to create instruments that provide information about the state of a student's knowledge, before, during, and after a course. For example, Lopez-Ramirez and Morales-Martinez (2019), Lopez et al (2014), Morales & Lopez (2016), Morales-Martinez, Lopez-Perez, et al (2020), Morales-Martinez et al (2021), Morales et al (2017) and Morales-Martinez et al (2015) have proposed the Chronometric Constructive Cognitive Learning Evaluation Model (C3-LEM), which suggests the use of cognitive tools to measure the cognitive properties of knowledge schemas learned in an academic environment. For example, this model measures what content is in a student's memory, how it is organized and structured, the temporal and dynamic patterns of these knowledge structures, and other aspects of a student's knowledge state.…”
Section: The Chronometric Constructive Cognitive Learning Evaluation Model (C3-lem)mentioning
confidence: 99%
“…Thus, the classifier uses a student's schema-related word-recognition times to assess whether the student has integrated new knowledge into long-term memory or has retained information in her/his short-term memory (e.g., to pass a test) or no new schemata were acquired at all. Figure 3B shows the role of this net classifier within a cognitive constructive-responsive/chronometric assessment of learning [38,39].…”
Section: Adaptive Instruction and The Constructive/chronometric E-assmentioning
confidence: 99%
“…In a functional adaptive instruction system such as the one shown in Figure 8, the student model is a domain-specific well-trained classifier. Empirical research in several knowledge domains has shown that this type of classifier yields successful classification in 95-98% of instances [38].…”
Section: The Student Modelmentioning
confidence: 99%